2007
DOI: 10.1152/ajpgi.00075.2007
|View full text |Cite
|
Sign up to set email alerts
|

Human organic anion transporter 1B1 and 1B3 function as bidirectional carriers and do not mediate GSH-bile acid cotransport

Abstract: Organic anion transporting polypeptides (OATP/SLCO) are generally believed to function as electroneutral anion exchangers, but direct evidence for this contention has only been provided for one member of this large family of genes, rat Oatp1a1/Oatp1 (Slco1a1). In contrast, a recent study has indicated that human OATP1B3/OATP-8 (SLCO1B3) functions as a GSH-bile acid cotransporter. The present study examined the transport mechanism and possible GSH requirement of the two members of this protein family that are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 31 publications
2
73
0
1
Order By: Relevance
“…Although OATP (human)/Oatp (rat, mouse) proteins were initially reported to mediate this exchange transport (57,58,62), a recent study has suggested that GSH/OA Ϫ exchange is not mediated by this family of transporters (65,66). We have previously detected the presence of mRNA for 7 different members of the SLCO/OATP family of transporters in Jurkat cells (13).…”
Section: Discussionmentioning
confidence: 97%
“…Although OATP (human)/Oatp (rat, mouse) proteins were initially reported to mediate this exchange transport (57,58,62), a recent study has suggested that GSH/OA Ϫ exchange is not mediated by this family of transporters (65,66). We have previously detected the presence of mRNA for 7 different members of the SLCO/OATP family of transporters in Jurkat cells (13).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a pH-driven transport of bile acids in these cells has also been reported (Marin et al, 2003). Although OATP1B3 has recently been suggested to be sensitive to activation by glutathione (Briz et al, 2006), this could not be confirmed by other authors (Mahagita et al, 2007). The reason for these controversial results may be due in part to the existence of artifactually induced acidification of local pH by addition of glutathione to insufficiently buffered media (Briz et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…The organic anion transporting polypeptides (OATP) have also been proposed to mediate GSH efflux by a GSH/OA À exchange, 40 although recent studies have suggested that GSH/OA À exchange is not mediated by this family of transporters. 41 Thus, there is a strong possibility that GSH efflux is mediated by a different and still uncharacterized entity. Whether GSH is depleted by its efflux, intracellular oxidation, or conjugation seems to depend on the nature and dose of the apoptotic stimuli.…”
Section: Figure 1 Apoptotic Signaling Pathways (See Text For Further mentioning
confidence: 99%